2021
DOI: 10.1097/mlr.0000000000001583
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Considerations in Incorporating Stakeholder Engagement Into a Palliative Care Transitions Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…All three measures have been developed through collaborative interdisciplinary efforts, have demonstrated reliability and validity, and, when used as a starting point for further investigation, can offer insights into the interplay between religion, spirituality, and medical-decision-making; yet only one, the FACIT-SP-12, involved patients in the initial stage of its development. This commitment to the principles of PCOR through which patients, who have a vested interest in a clinical decision and the evidence that supports that decision, participate in a measure's development (de Forcrand et al, 2021), likely contributed to the FACIT-Sp-12's strong psychometric properties, eventual translation into 39 different languages and widespread acceptance as a non-biased instrument capable of measuring meaning, peace, and faith in diverse religious and cultural contexts. While PCOR principles certainly offer a pathway to establishing content validity through the reflections and critical analysis of patients as participant stakeholders, there are no formal empirical tests for content validity and therefore no substitute for the contribution of subject matter experts.…”
Section: Discussionmentioning
confidence: 99%
“…All three measures have been developed through collaborative interdisciplinary efforts, have demonstrated reliability and validity, and, when used as a starting point for further investigation, can offer insights into the interplay between religion, spirituality, and medical-decision-making; yet only one, the FACIT-SP-12, involved patients in the initial stage of its development. This commitment to the principles of PCOR through which patients, who have a vested interest in a clinical decision and the evidence that supports that decision, participate in a measure's development (de Forcrand et al, 2021), likely contributed to the FACIT-Sp-12's strong psychometric properties, eventual translation into 39 different languages and widespread acceptance as a non-biased instrument capable of measuring meaning, peace, and faith in diverse religious and cultural contexts. While PCOR principles certainly offer a pathway to establishing content validity through the reflections and critical analysis of patients as participant stakeholders, there are no formal empirical tests for content validity and therefore no substitute for the contribution of subject matter experts.…”
Section: Discussionmentioning
confidence: 99%
“…Such a modification of the instrument, which takes the unique condition and situation of PAD into account, requires the involvement of stakeholders, such as patients and their caregivers, researchers, clinicians, instrument developers, advocacy groups, or others, across different stages of the instrument development process. Studies about stakeholder involvement and palliative care have shown that the engagement of stakeholders in research improves the research process and promotes more patient-centered results [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the issues of methods and scientific tools needed for evaluating stakeholders' level of engagement have been extensively debated into. 6 The author presents below the proposed framework within which (a) specific stakeholder groups and settings can be identified, and (b) effective PC care services can be ensured.…”
Section: Significance Of Stakeholders' Involvementmentioning
confidence: 99%